The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1971
DOI: 10.1111/j.1365-2141.1971.tb07037.x
|View full text |Cite
|
Sign up to set email alerts
|

Globin Synthesis in Sideroblastic Anaemia I α AND β PEPTIDE CHAIN SYNTHESIS

Abstract: Summary. The in vitro synthesis of the α and β peptide chains of globin have been measured in 11 patients suffering from sideroblastic anaemia (four congenital and seven idiopathic acquired). In the I0 patients who were anaemic the findings were similar. The synthesis of the globin chains was found to be defective in two respects; firstly, synthesis was asynchronous with an apparent deficiency of the synthesis of α chains, and, secondly, a large proportion of both α and β chains synthesized were not associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

1974
1974
1984
1984

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…There is good evidence that in iron deficiency anaemia both globin [21] and haem biosynthesis are disturbed [2,6]. Thus, various authors confirmed that in this condition the free erythrocyte protoporphyrin (EPP) is increased [8,14,16; Lyberatos et cl., unpublished data].…”
mentioning
confidence: 66%
“…There is good evidence that in iron deficiency anaemia both globin [21] and haem biosynthesis are disturbed [2,6]. Thus, various authors confirmed that in this condition the free erythrocyte protoporphyrin (EPP) is increased [8,14,16; Lyberatos et cl., unpublished data].…”
mentioning
confidence: 66%
“…Therefore, our observation of unbalanced synthesis with reduced non a / a ratio in CDA I and increased non a/a ratio in CDA I1 is at variance with the data available in the literature. Increased non a/a ratio has been recorded in sideroblastic anaemia (43). Although we did not study globin chain synthesis in bone marrow cells, it has been observed by other authors in various cases of CDA that unbalanced synthesis existed in precursor cells whenever it was recorded in peripheral blood (18,25,28,42).…”
Section: Discussionmentioning
confidence: 94%
“…Imbalance in a/fl synthesis with a-chain excess has been reported in patients with certain types of sideroblastic anemia l (22).…”
Section: Discussionmentioning
confidence: 99%